2016
DOI: 10.1175/mwr-d-15-0253.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diabatic Role of Ice Microphysical Processes in Two North Atlantic Summer Cyclones

Abstract: Numerical simulations are performed with the Weather Research and Forecasting Model to elucidate the diabatic effects of ice phase microphysical processes on the dynamics of two slow-moving summer cyclones that affected the United Kingdom during the summer of 2012. The first case is representative of a typical midlatitude storm for the time of year, while the second case is unusually deep. Sensitivity tests are performed with 5-km horizontal grid spacing and at lead times between 1 and 2 days using three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…Dearden et al [] used the WRF numerical model to simulate two summer cyclones to gain an understanding of sensitivities to ice microphysics, including the role of primary versus secondary ice formation. Primary ice formation describes the nucleation of new ice particles via homogenous freezing of liquid droplets at cold temperatures (< −37°C [ Koop et al , ]) or via heterogeneous processes involving ice nuclei [ Vali et al , ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dearden et al [] used the WRF numerical model to simulate two summer cyclones to gain an understanding of sensitivities to ice microphysics, including the role of primary versus secondary ice formation. Primary ice formation describes the nucleation of new ice particles via homogenous freezing of liquid droplets at cold temperatures (< −37°C [ Koop et al , ]) or via heterogeneous processes involving ice nuclei [ Vali et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Browning and Roberts [1994] further developed the understanding of frontal cyclones using model output and satellite images and discussed the dynamical factors leading to the formation of various cloud features. Dearden et al [2016] used the WRF numerical model to simulate two summer cyclones to gain an understanding of sensitivities to ice microphysics, including the role of primary versus secondary ice formation. Primary ice formation describes the nucleation of new ice particles via homogenous freezing of liquid droplets at cold temperatures (< À37°C [Koop et al, 2000]) or via heterogeneous processes involving ice nuclei [Vali et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that latent heating can play a significant role in the evolution of ETCs (e.g., Manabe 1956;Sanders and Gyakum 1980;Davis et al 1993;Zhu and Newell 1994;Stoelinga 1996;Pomroy and Thorpe 2000) though this can vary substantially on a case-to-case basis (e.g., Kuo and Low-Nam 1990;Smith 2000;Wernli et al 2002;Dacre and Gray 2009;Fink et al 2012;Dearden et al 2016). It has been shown that latent heating can significantly influence the evolution and deepening of some of the most damaging storms (e.g., Ulbrich et al 2001;Liberato et al 2011) and has been shown to influence frontal structure and propagation around ETCs (see Posselt and Martin 2004;Reeves and Lackmann 2004).…”
mentioning
confidence: 99%
“…This process is often called rime splintering or the Hallett-Mossop process (H-M process). Numerical models often use the Hallett-Mossop process to describe SIP (Field et al, 2017), using the same size threshold (droplets radius > 12 μm) and temperature range (À3 to À8°C; Connolly et al, 2006;Crawford et al, 2012;Dearden et al, 2016;Fridlind et al, 2007;Scott et al, 1977). Another study suggested that the concentration of cloud condensation nuclei (CCN) that affects the cloud droplet size distribution (Andreae et al, 2004;Braga et al, 2017;Mossop, 1985) has a greater influence on ice content in clouds via SIP than the actual INP concentration (Sullivan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%